Analisis Tipe Kompetisi, Dinamika Kestabilan Dan Peramalan Perolehan Laba Bersih Lembaga Keuangan Bank - Sri Wahyuni Jamal; Suparno Suparno; Fenty Fauziah; Marsha Anindita (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Competition in the business world is something that cannot be avoided, for example competition in the banking sector. In this sector, competition has the potential to encourage the business world to be more competitive, and also improve the efficiency and health of banks. The aim of this research is to analyze the competition that occurs between bank BNI and Mandiri using the Lotka-Volterra competition model approach. The results of this research indicate that the type of competition between bank BNI and Mandiri is the predatory-prey, where BNI acts as a prey, while Mandiri acts as a predator. In addition, the results of future net income forecasting show that BNI's net income tends to decline over the next ten years, and after that it will be stable. On the other hand, Mandiri's net income will increase over the next three years, with maximum net income obtained in 2025, and after that it will be stable. Therefore, both of them must adopt a policy to overcome net income which is likely to experience stagnation in the future. Keywords: bank, competition, Lotka-Volterra, net income, predatory, stable